Pengaruh Fear of Missing Out (FOMO) dan Social Media Marketing terhadap Niat Pembelian pada Produk Healthy - Noer, Lissa Rosdiana; Prihananto, Prahardika; Asokawati, Aqnis; Ninglasari, Sri Yayu; Rai, Ni Gusti Made (Institut Teknologi Sepuluh Nopember, 2024)
The food and beverage industry in Indonesia has stimulated a surge in Indonesian youth's practice of consuming nutritious food, resulting in fierce rivalry among enterprises in the healthy food sector. In order to manage the highly competitive business environment, organizations have increasingly resorted to utilizing social media marketing as a means to increase consumer inclination to make purchases. However, the widespread use of social media has led to concerns about individuals feeling excluded or perceived as outdated, a phenomenon commonly known as Fear of Missing Out (FOMO). The objective of this study is to examine the influence of Fear of Missing Out (FOMO) through social media marketing on consumers' inclination to make a purchase. We administered a survey using Google Forms to 120 participants aged between 18 and 34. We then analyzed the collected data using partial least squares structural equation modeling (PLS-SEM). The results indicate that both the fear of missing out (FOMO) and social media marketing have a beneficial impact on the desire to purchase healthy food goods. Utilizing the fear of missing out (FOMO) in social media marketing techniques can successfully enhance consumer attention and stimulate sales in the healthy food industry.